Efficient integration of HAPs and mobile satellites via free-space optical links - KORÇAK, ÖMER (ELSEVIER, 2011)
Non-geostationary (NGEO) mobile satellite systems integrated with High Altitude Platforms (HAPs) may have great potential in high capacity and real-time global telecommunications. We consider a system where HAPs are located above sensitive areas and transmit large amount of data to the terrestrial gateways via satellites using high capacity free-space optical links. In order to maximize availability and performance of this integrated system, optical link establishment between HAPs and mobile satellites with limited resources should be optimized. In this paper, we formulate an optimization problem for matching HAPs and satellites in such a way that the utilization of HAPs is maximized together with the average elevation angle between HAPs and satellites. We also propose a method to avoid frequent switching of optical links. We come up with a polynomial-time solution approach for the formulated problem, demonstrate numerical results in sample scenarios for various system parameters, and discuss the reasonable selection of these variables. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: High Altitude Platform; Free-space optical link; Satellite network; HIGH-ALTITUDE PLATFORMS